2003
DOI: 10.1007/s00421-002-0757-3
|View full text |Cite
|
Sign up to set email alerts
|

Delayed reoxygenation after maximal isometric handgrip exercise in high oxidative capacity muscle

Abstract: We hypothesized that after maximal short-term isometric exercise, when O(2) demand is still high and O(2) supply is not fully activated, higher oxidative capacity muscle may exhibit slower muscle reoxygenation after the exercise than low oxidative capacity muscle. Seven healthy male subjects performed a maximal voluntary isometric handgrip exercise for 10 s. The reoxygenation rate after the exercise (Reoxy-rate) in the finger flexor muscle was determined by near infrared continuous wave spectroscopy (NIRcws) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 42 publications
4
39
2
Order By: Relevance
“…In the present study, during the 2-min between-sprint recovery periods, muscle oxygenation returned to pre-exercise levels (Fig. 4), indicating a possible recovery of muscle PCr (McCully et al 1994;Kime et al 2003). Previous data have nevertheless shown that the 2 min duration may be insufficient for the complete recovery of muscle metabolites related to repeated-sprint ability.…”
Section: Changes In Muscle Oxygenation With Sitsupporting
confidence: 54%
“…In the present study, during the 2-min between-sprint recovery periods, muscle oxygenation returned to pre-exercise levels (Fig. 4), indicating a possible recovery of muscle PCr (McCully et al 1994;Kime et al 2003). Previous data have nevertheless shown that the 2 min duration may be insufficient for the complete recovery of muscle metabolites related to repeated-sprint ability.…”
Section: Changes In Muscle Oxygenation With Sitsupporting
confidence: 54%
“…However, it seems likely that oxidative metabolism during maximal contractions was similar between EMS and VOL in this study, which resulted in the similar recovery responses of DTOI and DtHb. Since recovery of DTOI after exercise is related to PCr resynthesis and/or rate of blood flow/oxygen supply (Hamaoka et al 2007;Kime et al 2003), the similar Fig. 2 Changes (mean ± SEM) in biceps brachii DTOI during 30% MVC and maximal intensity repetitive isometric contractions of the elbow flexor muscles for the electrically evoked (EMS) and VOL sessions.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, we used a linear model (adapted from Kime et al 2003a), which was well suited to both TSI changes and the short between-sprints recovery periods. The most important finding is that, once adjusted for changes in S1 performance, the improvements in repeated-sprint ability (%Dec was substantially improved during both RS adj and RS post, Table 1) were moderately-to-largely related to improvements in Reoxy rate (r = -0.52 and -0.40).…”
Section: Effect Of Endurance Training On Repeated-sprint Performancementioning
confidence: 99%
“…1, 2). Therefore, for simplicity and to use a similar (and more appropriate) modeling for both S1 and S2, a linear model was fitted to the linear part of the TSI (both absolute and normalized values) versus time relationship within the first 15 s of recovery (adapted from Kime et al 2003a). The slope of the relationship was retained as an index of reoxygenation rate (Reoxy Rate, % s -1 ).…”
Section: Near-infrared Spectroscopy Measurementsmentioning
confidence: 99%